2017
DOI: 10.1002/hpm.2450
|View full text |Cite
|
Sign up to set email alerts
|

Programmes for the prevention of parent‐to‐child transmission of HIV in Papua New Guinea: Health system challenges and opportunities

Abstract: The study findings highlight an important need for investment in appropriately trained and supported HCWs and integration of services at each stage of the PPTCT programme. Lessons from the PPTCT experience in PNG may inform policy discussions and considerations in other similar contexts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…21 Importantly, these key drivers of sustainability have been reported by health workers as significant challenges within the current PMTCT programme in PNG. 38 Ensuring adequate resources to follow-up patients was identified in our study as an important component of sustainable scale-up of the Xpert HIV-1 Qualitative test.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…21 Importantly, these key drivers of sustainability have been reported by health workers as significant challenges within the current PMTCT programme in PNG. 38 Ensuring adequate resources to follow-up patients was identified in our study as an important component of sustainable scale-up of the Xpert HIV-1 Qualitative test.…”
Section: Discussionmentioning
confidence: 93%
“…Tynan et al 38 also describe patient follow-up as a pervasive barrier to successful implementation of the PMTCT programme in PNG. It is, however, worth noting that the availability of POC EID testing is likely to reduce the need for active tracing of mother-infant pairs for results communication compared with standard care DBS testing.…”
Section: Discussionmentioning
confidence: 99%
“…PNG-specific may not be generalisable to the Pacific region. 5 Tynan [45] 2018 PNG To examine healthcare worker perceptions of health system factors impacting on the performance of Prevention of Parent to Child (PPTCT) programmes. Descriptive study Qualitative – semi-structured interviews with healthcare workers involved in the program.…”
Section: Resultsmentioning
confidence: 99%
“…Other interventions included a contraceptive implant outreach service [44] , prevention of parent to child HIV transmission programs [45] , development of maternal and newborn health action plans [31] , reviews of national clinical policies and standards [29] , midwifery leadership programs [46] and the formation of Public Private Partnerships at regional and national levels [ 31 , 47 ]. Proportion of Australian and international participants who were knowledgeable and confident regarding management of perinatal deaths increased from pre-to post-workshop for all items and stations (p < 0.001).…”
Section: Overview Of Quality Improvement Interventionsmentioning
confidence: 99%
“…The healthcare system is largely decentralized in PNG, where religious organisations play a significant role in health service delivery in rural areas ( Grundy et al, 2019 ). Significant gaps in the number, diversity and distribution of the health workforce in PNG has been recognised, leading to staff taking on additional roles and responsibilities ( Grundy et al, 2019 , Tynan et al, 2017 ). Findings from our study showed that the number of staff trained in swabbing was not congruent with workforce needs in health centres.…”
Section: Discussionmentioning
confidence: 99%